Opening Doors : Gender Equality in the Middle East And North Africa - Vishwanath, Tara (World Bank, Washington, DC, 2012)
Many countries in the Middle East and North Africa (MENA) region are undergoing a profound transformation. From Morocco to Yemen, popular movements have called for reforms to make government more inclusive and more accountable, extend social and economic freedoms, and boost employment opportunities. Young men and women have been at the forefront of these calls for change, reflecting their desire to participate actively in the political sphere. As new governments are being formed in Tunisia and Egypt, and elections are underway elsewhere in the region, people continue to demonstrate for meaningful change. It is now clear that the rapid transformation that seemed so close at the start of the Arab Spring is in fact likely to be a process of gradual change that will take months, if not years. This quick note is based on a report which complements the 2012 World Development Report (WDR) on Gender Equality and Development, focusing on challenges and reform priorities for gender equality in the MENA region. The approach of the WDR 2012, the report draws on economic analysis of quantitative data from countries in the region, qualitative research and other international evidence.